Biomechanical modelling of diabetic foot ulcers: A computational study. (11th October 2021) - Singh, Gurpreet; Gupta, Shubham; Chanda, Arnab
Abstract: Diabetic foot problems are widespread globally, resulting in substantial medical, economic, and social challenges for patients and their families. Among diabetic complications, foot ulceration is the most frequent outcome and is more probable to be of neuropathic origin. To date, a plethora of studies has focused on diabetic foot and ulcer prevention. However, limited studies have investigated the biomechanics of diabetic foot post ulceration. In this work, extensive biomechanical modelling of diabetic foot ulcers was attempted. A full-scale foot model was developed using measurements from a human subject, and ulcers of differing sizes and depths were modelled at different plantar sites numerically. Also, the foot model was computationally modified to study the effect of flat foot conditions on the same diabetic ulcers. Standing condition was simulated, and the induced stresses were investigated at the plantar region. The maximum stresses were observed to be similar for all ulcer sizes and depths at the lateral midfoot region of the normal foot. However, the maximum stresses were reported in the lateral heel region for the flat foot, which varied significantly with size and depth. Such results present important information on the foot condition post ulceration and may help identify possibilities of further ulceration in the diabetic foot. These novel findings are anticipated to be indispensable for the development of suitable interventions (e.g., custom orthotics) for diabetic foot ulcer management.